Factors Associated with Comfort Discussing PrEP with Healthcare Providers among Black Cisgender Women - Whitney C. Irie; Anais Mahone; Raja Nakka; Musie Ghebremichael (Tropical Medicine and Infectious Disease, 2023)
Preexposure prophylaxis (PrEP) for HIV prevention uptake remains low among Black cisgender women in the United States, despite their disproportionate HIV burden. This study aimed to examine factors associated with Black women’s comfort discussing PrEP with healthcare providers and its link to their interest in PrEP use. A cross-sectional survey was conducted with a national sample of 315 Black cisgender women. Descriptive statistics and logistic regression models were utilized for data analysis. The results showed that 79% of Black women felt comfortable discussing PrEP with their healthcare provider. Age, recent healthcare provider visit, interest in PrEP, and positive social norms were associated with increased odds of comfort in discussing PrEP, while anticipated PrEP disapproval and stigma were associated with decreased odds. Older age was related to greater comfort, potentially due to increased familiarity and self-efficacy in discussing sexual health. Recent healthcare utilization indicated positive provider relationships, facilitating discussions about sexual health. Anticipating support from social networks positively influenced comfort levels. Conversely, PrEP-related stigma and anticipated disapproval were barriers to comfort. These findings highlight the importance of provider–patient communication and social support in facilitating PrEP engagement among Black cisgender women. Interventions should consider age-appropriate strategies and address structural and provider biases to improve PrEP discussions and promote HIV prevention.